2019
DOI: 10.1186/s12934-019-1169-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an acetyl xylan esterase from the marine bacterium Ochrovirga pacifica and its synergism with xylanase on beechwood xylan

Abstract: Background Acetyl xylan esterase plays an important role in the complete enzymatic hydrolysis of lignocellulosic materials. It hydrolyzes the ester linkages of acetic acid in xylan and supports and enhances the activity of xylanase. This study was conducted to identify and overexpress the acetyl xylan esterase (AXE) gene revealed by the genomic sequencing of the marine bacterium Ochrovirga pacifica . Results The AXE gene has an 864-bp open rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
0
23
1
Order By: Relevance
“…xylans). Characterisation of CE15 and CE7 from marine microbes is rare, though activity on xylans, which are a structural component of marine algae, has previously been demonstrated [ 55 57 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…xylans). Characterisation of CE15 and CE7 from marine microbes is rare, though activity on xylans, which are a structural component of marine algae, has previously been demonstrated [ 55 57 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on the synergism between xylanases and acetyl xylan esterases reported by Hettiarachchi et al and Yang et al [ 19 , 38 ] showed the removal of acetyl groups in xylan and improvement in xylan hydrolysis. Experiments were performed to investigate the synergetic effect of XynS1 derived from Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%
“…AXE derived from the marine bacteria O. pacifica was used to investigate the synergetic effect with rXynS1 on xylan hydrolysis. According to the results of conserved domain analysis, the AXE derived from O. pacifica has been classified under the alpha/beta hydrolase family [ 19 ]. Mn 2+ was used in the experiment as Mn 2+ can improve the enzymatic activities of rXynS1 and AXE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations